Tradisional ABC Lima Dasar pada Pembelajaran PAI di SMK Al-Fudlola’ Porong Sidoarjo - Wulandari, Feby Cahyani; Kirom, Askhabul; Mohtarom, Ali; Yusuf, Achmad (LPPM Institut Pendidikan Nusantara Global, 2024)
This research and development aims to produce a learning model based on the traditional ABC Lima Dasar games that is effective and feasible for PAI learning at Al-Fudlola' Porong Sidoarjo Vocational School . This model was developed through a Research and Development (R&D) approach using the 4D development model, namely define, design stage, develop stage, disseminate stage. Data collection techniques use observation, interviews, and questionnaires. The game-based learning model as a learning model provides opportunities for students to interact, collaborate and explore actively in PAI learning. The results found that the Five Basic ABC learning model had a positive impact on students' cognitive, spiritual, emotional, language and socio-cultural abilities. The research results show students' positive response to this learning, describing the Five Basic ABC model as an effective, innovative alternative in PAI learning at Al-Fudlola' Porong Sidoarjo Vocational School.